(3GdUMGaI GdeJNUUI (B:s (3GdSjGSI GdNGQLjI(B- (3GdeQCI(B- (3GdQjGVjI(B- (3GdLQjeI(B- (3Gdaf (B/s - (3CHhRjO, aGQhbs ((3GdbGgQI (B:s (3YGde GdcJH ,s, 1986)
(3jJVef cd aUd ef aUhd GdOQGSI GdNeSI eHMKjf JfGhd GdGhd GdJZWjI GdUMajI HjfeG YGdL GdeHMK GdKGfj GSGdjH GdcJGHI GdUMajI aj GdUMGaI GdeJNUUIs
Keywords: (3GdUMGaIs; (3GdUMGaI GdeJNUUIs; (3GdcJGHI GdUMajIs